A quantitative study to investigate and explore the retention of theoretical knowledge of Basic Life Support amongst pre-registration student nurses - Poole, Laura (2011)
The acquisition and retention of both basic life support (BLS) theoretical knowledge and practical skills are regarded as essential for all healthcare professionals; including student nurses. Whilst there appears to be an abundance of literature regarding the practical and theoretical BLS competency of registered nurses, this appears to be less well documented amongst the student nurse population. The purpose of this study was to therefore, add to the existing body of knowledge regarding the retention of theoretical BLS knowledge amongst a sample of nursing students. Utilising a quantitative, cross-sectional design, 202 questionnaires were distributed to a sample of student nurses prior to their annual BLS mandatory training, who were studying on the Master of Nursing Science programme. The questionnaire sought to ascertain overall BLS knowledge; identify areas of BLS knowledge deficit; and examine the value of additional experience and confidence in relation to the participants‟ knowledge score. 177 questionnaires were returned, providing an impressive total response rate of 87.6%. The results identified general insufficiencies in the students‟ BLS knowledge, which correlated with the previously conducted research within this area. Only 26 (14.7%) of participants achieved the „pass‟ criteria set for the paper, and no one achieved 100%. The study did, however, find statistically significant differences between a student‟s knowledge and stage of their training; their confidence; their additional experience and whether they had performed BLS themselves. Though there are various methodological weaknesses and limitations of this study, particularly with regards to the overall study design and restrictive sample, this study has prompted the identification of a variety of further recommendations for future nursing research, education and practice.